SAT0464 Metabolic Effects in Skeletal Muscle of Endurance Exercise in Patients with Polymyositis and Dermatomyositis: A Pilot Study. (9th June 2015) - Alemo Munters, L.; Dastmalchi, M.; Lindroos, E.; Ottosson, C.; Alexanderson, H.; Crofford, L.J.; Lundberg, I.E.
Abstract : Background: Insulin resistance in skeletal muscle is a feature of the metabolic syndrome, which is highly prevalent in patients with dermatomyositis (DM)(1). The homeostasis assessment (HOMA) measures insulin sensitivity and correlates highly with interstitial glycerol. Insulin sensitivity is increased by physical exercise. Metabolic effects of physical exercise in skeletal muscle are incompletely known in patients with polymyositis (PM) and DM. Objectives: We hypothesized that patients with PM/DM would have altered glycerol levels in muscle tissue compared to matched healthy controls (HC). Furthermore, physical endurance exercise training would normalize muscle tissue metabolism and improve muscle performance in PM/DM. Methods: In the first part of this study interstitial glycerol levels in skeletal muscle were compared between patients with PM/DM (n=23) in an established disease phase (duration since diagnosis, Median 7 years (Range, 1-33); age, 58 years (37-77) and sex ( n, female/male), 17/6) and matched HC (n=12). In the second part interstitial glycerol levels in skeletal muscle were measured in a controlled trial evaluating effects of a 12 week endurance exercise program in patients with PM/DM (EG, n=9) compared to a non-exercising control group with PM/DM (CG, n=7). Interstitial glycerol was measured in vastus lateralis muscle with microdialysis. The change in glycerol levels (Δglycerol) from at rest to after cycling to exhaustion was used as a marker of metabolic capacity. Muscle performance was assessed as the cycling time to exhaustion at 65% of VO2 max and 5 voluntary repetition maximum (5VRM) in knee extensors. Mann-Whitney test was used for between group comparison at baseline, Wilcoxon test for paired analysis and Fishers exact test to investigate difference between the EG and the CG as to frequency of responders and non-responders. P<0.05 was considered statistically significant. Results: Patients had lower Δglycerol in muscle tissue (Median, 113 μmol/l (IQR, 75) compared to HC 175 μmol/l (137), (p<0.05)). Following 12 week endurance training, the EG increased in muscle Δglycerol from 109 μmol/l (23) to 154 μmol/l (69) (p<0.05), while no changes were observed in the CG (112 μmol/l (73) to 110 μmol/l (77), (NS)). These metabolic changes in skeletal muscle in the EG were concurrent with improved muscle performance. A majority in the EG improved compared to the CG in Δglycerol (8 in the EG versus 2 in the CG) (p<0.05), cycling time (9 versus 1) (p<0.01) and in 5VRM (6 versus none) (p<0.05). Conclusions: Patients with established PM/DM have a lower metabolic capacity in their skeletal muscles compared to healthy individuals. Endurance exercise may improve metabolic muscle health and increases insulin sensitivity in skeletal muscle in PM/DM and may thereby potentially prevent or reduce the risk of developing the metabolic syndrome and its risk factors such as cardiovascular disease. References: de Moraes MT, et al (2013) An analysis of metabolic syndrome in adult dermatomyositis with a focus on cardiovascular disease. Arthritis Care Res 65: 793–799. Disclosure of Interest: None declared